Law of Commercial Transactions - Mayer, Don; Warner, Daniel; Siedel, George J.; Lieberman, Jethro K. (Open textbook library., 2012)
Law of Commercial Transactions is an up-to-date textbook that covers legal issues that students who engage in commercial transactions must understand. The text is organized to permit instructors to tailor the materials to their particular approach. The authors take special care to engage students by relating law to everyday events with their clear, concise and readable style. After introductory chapters covering the legal environment of business, Law of Commercial Transactions provides students with context and essential legal concepts relating to key commercial transactions topics: contracts, sales, commercial paper, debtors and creditors. The text provides the vocabulary and legal savvy students will need to talk in an educated way to customers, suppliers, creditors, government regulators and other stakeholders — and to their own lawyers.